The Mediating Role of Ethical Atmosphere in the Influence of Religious Work Ethic on Deviant Behaviour - Amin Wahyudi (Asosiasi Peneliti Manajemen Adat Indonesia, 2018)
This study aimed to analyze the influence of religious work ethic on deviant behavior and mediating role of ethical atmosphere. The study design is corelational research. Variables in this research are deviant behavior, religious work ethic and ethical atmosphere as mediating variable. The population in this study were employees of government offices, universities, hospitals, schools in region of Surakarta. The samples this study are 100 people participant with conveniance sampling techniques. The analysis in this research used with path analysis by multiple linear regression. This study are expected to provide benefit in further developing a model that describes the concept of the religious work ethic with deviant behaviors of human resources in an organization. The results show that there is a negative and significant influence religious work ethics and athic atmosphere on deviant behavior, there is a positive and significant influence religious work ethic on ethical atmosphere. The conclution of this study that religious work ethics and ethical atmosphere are very important for development of human resources behavior.